2016
DOI: 10.3906/sag-1411-157
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the TIMI risk index on admission for predicting angiographic no-reflow after primary percutaneous coronary intervention in patients with STEMI

Abstract: Background/aim: The thrombolysis in myocardial infarction (TIMI) risk score (TRS), and the TIMI risk index (TRI) have been reported in coronary artery disease patients. We investigated whether admission TRI is associated with no-reflow (NRF) in patients undergoing primary percutaneous coronary intervention (p-PCI).Materials and methods: ST-segment elevation myocardial infarction (STEMI) patients treated with p-PCI were included in the study. TRI was calculated on admission using specified variables. We defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In a similar line to a past study, our findings demonstrated a significant relationship between TIMI risk score and no-reflow. 27 Of note, we found the TIMI risk score as an independent predictor of no-reflow. TIMI risk score includes clinical variables like age, diabetes mellitus/ hypertension/angina, blood pressure, heart rate, Killip class, weight, anterior ST-elevation or left bundle branch block, and time to treatment.…”
Section: Discussionmentioning
confidence: 62%
“…In a similar line to a past study, our findings demonstrated a significant relationship between TIMI risk score and no-reflow. 27 Of note, we found the TIMI risk score as an independent predictor of no-reflow. TIMI risk score includes clinical variables like age, diabetes mellitus/ hypertension/angina, blood pressure, heart rate, Killip class, weight, anterior ST-elevation or left bundle branch block, and time to treatment.…”
Section: Discussionmentioning
confidence: 62%
“…The TIMI risk score used to evaluate the in-hospital prognosis in patients with STEMI, the TIMI risk index, which Acet et al 40 showed can predict angiographic NR and the score devised by Bayramoğlu and colleagues, 41 consisting of 7 parameters, are some of the scoring methods that can be used for NR. There are studies supporting the relationship between NR and the CHA 2 DS 2 -Vasc score, which is among these risk scores and is considered to be a prognostic marker for many cardiac conditions.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 also plays an important role in endothelial inflammation and the formation of atherosclerotic plaques 18 . Additionally, the network structure of stents can aggravate microcirculation dysfunction to induce chemotaxis and trigger monocyte activation to secrete various vasoactive factors like ET-1 and VCAM-1, which in turn induce the onset of reperfusion injury 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%